Kajian Integrasi Nilai-Nilai Karakter Islami Peserta Didik dalam Materi Hidrokarbon di Sekolah Menegah Kejuruan - Lis Setiyo Ningrum; Sri Haryani; Kasmadi Imam Supardi (Universitas Syiah Kuala, 2020)
The inculcation of Islamic character values for students is an important thing to be taught to students. One way of planting is to integrate learning material with the values of Islamic characters of students. This research was carried out through exploring the values of Islamic characters in hydrocarbon material taught in vocational high schools. The purpose of this study is to integrate the values of Islamic characters that are reinforced in the hydrocarbon material in schools. This research is a literature study with qualitative descriptive methods using content analysis techniques, analysis with a philosophical approach, analysis with triadic models, and analysis with confirmation models. The results obtained in this study are the study of the integration of hydrocarbon material chemistry lessons and Islamic character values that can be taught to intermediate level students. The results of the integration are as follows (1) The conversion of a less useful item into a more useful item, (2) Preserving nature as the human task as a Khalifah on earth, (3) Utilizing one of the reactions that occur in hydrocarbon compounds in daily life, (4) Utilizing petroleum as an example of a hydrocarbon product that is very beneficial to humans, (5) The benefits of carbon atoms in the carbon cycle, (6) The benefits of hydrocarbons in photosynthesis to increase our gratitude to Allah SWT, (7 ) The benefits of the special carbon atom in the concept of pairing in life, and (8) Grateful for the greatness of God who has created everything in nature